Consumer acceptance of milk from goats fed a diet supplemented with aromatic plants. (6th October 2016) - Boutoial, Khalid; García, Víctor; Rovira, Silvia; Ferrandini, Eduardo; López, María Belén
Abstract : Although Spain is an important producer of goat milk, less than 2% of this milk is used for direct consumption. The aim of this study was to evaluate the consumer acceptance of milk obtained from goats fed a diet supplemented with aromatic plants as a source of natural antioxidants, in this case distilled thyme and rosemary leaves and nondistilled thyme leaves. A paired comparison test identified significant differences between the control milk and all those obtained from goats receiving supplemented diets.